Accelerometry of Seabream in a Sea-Cage: Is Acceleration a Good Proxy for Activity? - Palstra, Arjan P.; Arechavala-Lopez, Pablo; Xue, Yuanxu; Roque, Ana (Frontiers in Marine Science, 2021)
Activity assessment of individual fish in a sea-cage could provide valuable insights into the behavior, but also physiological well-being and resilience, of the fish population in the cage. Acceleration can be monitored continuously with internal acoustic transmitter tags and is generally applied as a real-time proxy for activity. The objective of this study was to investigate the activity patterns of Gilthead seabream (Sparus aurata) by transmitter tags in a sea-cage and analyze correlations with water temperature, fish size and tissue weights. Experimental fish (N=300) were transferred to an experimental sea-cage of which thirty fish (Standard Length SL= 18.3 ±1.7 cm; Body Weight BW= 174 ± 39 g) were implanted with accelerometer tags. Accelerations were monitored for a period of 6 weeks (Nov.-Dec.) and were analyzed over the 6 weeks and 24 hours of the day. At the end of the experimental period, tagged fish were again measured, weighed and dissected for tissue and fillet weights, and correlations with accelerations were analyzed. Daily rhythms in accelerations under the experimental conditions were characterized by more active periods from 6 to 14 h and 18 to 0 h and less active periods from 0 to 6 h and 14 to 18 h. This W-shaped pattern remained over the experimental weeks, even with diurnal accelerations decreasing which was correlated to the dropping temperature. The increase in activity was not during, but just before feeding indicating food-anticipatory activity. Activity patterning can be useful for timing feeding events at the start of active periods, in this study between 6 and 11 h, and between 18 and 22 h. Acceleration was negatively correlated to heart and mesenteric fat mass, which was the exact contrary of our expectations for sustainedly swimming seabream. These results suggest that acceleration is a proxy for unsteady swimming activity only and research is required into the accelerations occurring during sustained swimming of seabream at various speeds.